Comprehensive assessment of long-term IASI NH3 retrievals: Spatial patterns and region-specific emission profiles for agriculture - Tokgoz, Seda; Akyuz, Ezgi; Alban, Aykut Mehmet; Saracoglu, Serra; Kaynak, Burcak (ELSEVIER, 2026)
Agricultural emission rates and atmospheric NH3 levels are very sensitive to agricultural practices and meteorological factors such as temperature, wind speed, and precipitation. With climate change, these impacts on agricultural NH3 emissions become more important, and updates are necessary in emission estimates and their spatio-temporal distributions. NH3 is a pollutant, and a significant precursor to secondary inorganic aerosol formation. In this study, twelve years (2012-2023) of NH3 retrievals were utilized to obtain annual, monthly, and longterm monthly NH3 distributions with 36 & times; 36km2 grids for Europe (EU) and 4 & times; 4km2 grids covering T & uuml;rkiye (TR) and surrounding regions. Long-term trend analysis indicated high regional enhancements over Poland, Lithuania, and Latvia in addition to T & uuml;rkiye and Iraq. Highest drops were observed in northern Albania, Montenegro, and southern Bosnia and Herzegovina. In T & uuml;rkiye, although the reported emission levels did not change significantly, there was a remarkable increase in NH3 levels and an expansion of hotspot regions with an overall increase. Long-term averages of monthly distributions revealed different times of maximum values indicating that peak levels were observed in April for northern Europe, whereas lower regions have maximums in June-August. T & uuml;rkiye, in particular, showed a regional maximum shift starting in May in central and southeastern regions to July-August in the Aegean and Mediterranean regions. Levels were found to be significantly high in October and November, unlike in Europe. Together, these findings indicate significant regional and temporal variability in NH3 concentrations, including substantial seasonal differences. Cluster analysis showed four out of six (EU) and five out of eight (TR) distinct clusters associated with agricultural activities, confirming the combined effect of agricultural emissions and meteorology. Principal Component Analysis (PCA) indicated two major PCs associated with agriculture, which explained a total of 43.7% (EU) and 30.5% (TR) of the variability. Lastly, region-specific temporal profiles were proposed for nine agricultural regions in T & uuml;rkiye for agricultural sub-sectors, along with aggregated K-AgriLivestock (manure management) and L-AgriOther (crop production) sectors. These profiles were also found consistent with TR-PC1 and PC2 average monthly profiles. This study provides a new approach to the assessment of agricultural NH3 variability combining long-term IASI NH3 retrievals, PCA/CA, and local agricultural practices to propose, for the first time, NH3 seasonal emission profiles for nine agricultural regions in T & uuml;rkiye. These temporal profiles will improve the performance of regional air quality models as inputs.
Keywords: NH3; Agriculture; Cluster analysis; PCA; Temporal profile; AMMONIA EMISSIONS; ATMOSPHERIC CHEMISTRY; POINT SOURCES; NITROGEN; CHINA; MODEL; VARIABILITY; FRAMEWORK; TRENDS; SLURRY; Forestry; Meteorology & Atmospheric Sciences